Can Tax Avoidance Be a Moderator in the Relationship Between Earnings Management and Firm Value? - Firmansyah, Amrie; Amanta, Hafiz Putra; Kartiko, Nafis Dwi (Accounting Analysis Journal, 2025)
Purpose: The study examines the effect of earnings management on firm value and investigates whether tax avoidance moderates this relationship in the context of the Indonesian capital market. The research is motivated by concerns about financial transparency and corporate credibility in emerging markets, where weak enforcement and managerial discretion often influence investor confidence. Method: The study uses panel data of 3,835 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange during 2010–2022. Samples were selected through purposive sampling based on data completeness and reporting consistency. Multiple regression analysis is employed to test the proposed hypotheses. Findings:  The result reveals that earnings management significantly reduces firm value, confirming that discretionary financial reporting practices weaken market confidence. Meanwhile, tax avoidance does not strengthen this negative effect, indicating that investors view tax minimization independently from earnings management behavior. Novelty: The study provides empirical evidence from an emerging market showing that tax avoidance does not amplify the adverse market perception of earnings management. The findings emphasize that investor responses in Indonesia are shaped more by earnings quality than tax strategies.